Penggunaan Model Problem Based Learning (PBL) untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Rismawanti Putri (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The Problem-Based Learning (PBL) model was implemented with 12 fifth-grade students (6 boys, 6 girls) to enhance critical thinking skills in understanding the "Changing Earth" material. Conventional teaching methods were deemed insufficient in stimulating critical thought and in-depth comprehension of this complex concept. The structured PBL implementation spanned from problem orientation to evaluation, conducted in the classroom according to the schedule. Formative assessments through observation and worksheets, along with summative evaluations, demonstrated success with improved student understanding, with most achieving the Minimum Completeness Criteria (KKM). Student interaction and enthusiasm increased, and critical thinking abilities began to develop, fostered by the teacher's positive reinforcement and appreciation. The success was evident in the students' ability to analyze the impact of human activities and natural disasters on Earth's changes. However, a primary obstacle was the limited time for group discussions and presentations, resulting in only one group having the opportunity to present their findings. A proposed solution to overcome this time constraint is to divide the discussion and presentation activities into multiple learning sessions for more effective time management.